The analytical model of wireless LAN - Дишлюк, О. М. (Problems of Informatization and Control, 2008)
Considered Wireless LAN. As the communication channel in a wireless network has limited bandwidth and used simultaneously by all stations, the process of functioning of such a network can be modeled using random multiple access protocols. To describe and build analytical models used wireless network queuing system with repeated calls. Defined probability distribution channel conditions and basic imovirnisno-temporal characteristics of network